(untitled) (CIPEEX, 2025)
Humanization in healthcare encompasses comprehensive patient care, assistance that goes beyond the disease to address the individual as a whole. These characteristics depend largely on medical education, which should aim to train humanized professionals. Given this, the present study aims to investigate patients’ perceptions of the relevance of humanized care provided by eighth-semester medical students, all from the medical course at the Evangelical University of Goiás – UniEVANGÉLICA, at the Central University Outpatient Clinic, in the city of Anápolis, Goiás. This is a cross-sectional, observational, analytical study of a quantitative nature, with patients enrolled in the Unified Health System (SUS) as the target audience. The patients evaluated perceived the care as impersonal and focused on the physician and the disease. The humanization of medical care faces significant challenges, such as work overload and lack of communication, which hinder the physician-patient relationship. Improving communication and adopting more patient-centered practices are essential to creating a more welcoming and effective environment.